Legislative interventions for educators in ensuring the right of access to quality education in South Africa - Mantshiu, Shibe Rachel (My University, 2017)
This study focuses on the legislative interventions for educators in ensuring the right of access to quality education in South Africa. It highlights the right of access to education as provided in section 29 of the Constitution of the Republic of South Africa. It examines the effect of poor education to the black majority and qualifications of educators during the apartheid period and how this has impacted black schools and learners. The structures, policies and programs of the apartheid are compared and contrasted to the post- apartheid (1994) structures, policies and programs. It argues that poor performance in black schools emanates from incapacity of educators in providing quality education. Although there was a radical transition in educational laws and programs from apartheid to post- apartheid, till date there are still challenges in the implementation of these policies and laws. The mini-dissertation recommends that government must capacitate and empower educators as this will enable them to deliver high standard pedagogy in black schools.
Thesis (M. Dev.) -- University of Limpopo, 2017.
Keywords: Educators; Education access; Constitution of the Republic of South Africa; xii, 64 leaves; Education - South Africa